STRENGTHENING OF SCHOOL QUALITY THROUGH SCHOOL PRINCIPAL LEADERSHIP - Wresni Pujiyati (International Journal of Educational Management and Innovation, 2020)
This study aims to analyze and find out the implementation of principals 'leadership through school quality with the long-term goal of improving the quality of schools through principals' leadership. The specific target of this research is to develop a principal's leadership model. The research method uses a qualitative approach through case studies through observation, interviews, document studies relating to the principal's leadership and school quality. The general conclusion is that improving school quality is a process towards the realization of quality schools. Principal's leadership in strengthening school quality can be found in (1) Improving school quality (2) Principal's leadership strategy in improving school quality.